2020
DOI: 10.12968/bjon.2020.29.8.s44
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-detected venous changes associated with peripheral intravenous placement in children

Abstract: HIGHLIGHTS Ultrasound shows several venous changes in pediatric PIV-containing veins. Changes were visualized by ultrasound in the absence of physical exam findings. Venous luminal narrowing, wall thickening, and thrombosis may explain PIV failure. Background: Peripheral intravenous catheters (PIVs) are routinely used for venous access in hospitalized pediatric patients to administer fluids and medications and to aspirate blood. Unfortunately, PIVs do not remain functional for the entire duration of intravascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This current assessment method does not capture the evolution and progression of the cause that ultimately leads to catheter failure until it is too late. Some recent exploratory research using ultrasound technology determined that changes in the vein and soft tissue often occur after PIVC insertion [ 9 ]. Internally, venous and soft tissue changes may include: narrowing of the vein wall, vein wall thickening, subcutaneous edema, and presence of thrombus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current assessment method does not capture the evolution and progression of the cause that ultimately leads to catheter failure until it is too late. Some recent exploratory research using ultrasound technology determined that changes in the vein and soft tissue often occur after PIVC insertion [ 9 ]. Internally, venous and soft tissue changes may include: narrowing of the vein wall, vein wall thickening, subcutaneous edema, and presence of thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…Internally, venous and soft tissue changes may include: narrowing of the vein wall, vein wall thickening, subcutaneous edema, and presence of thrombus. These changes can occur even in the absence of any clinical signs or symptoms evident on external exam [ 9 ]. While the literature has demonstrated that ultrasound is capable of identifying these subcutaneous changes, how well they correlate with impending or ongoing PIVC failure remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These changes lead to restricted blood flow at the IV catheter tip and the inability to access downstream collateral circulation because of venous valves preventing retrograde blood flow to the IV catheter. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…9 Prevention of these complications requires focusing on the changes beneath the skin that begin soon after PIVC insertion and progress over time. 10,11 Thus, investigating the anatomical changes at the subcutaneous level after PIVC insertion may unlock the secret to improved survivorship. Some recent exploratory data indicates that PIVC failure is due to ongoing in ammation of the vein.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Internally, venous changes can include narrowing of vein wall, wall thickening, and presence of thrombus even in the absence of any clinical signs and symptoms. 11 The incorporation of venous duplex ultrasonography to the site evaluation provides an objective means to characterize the ongoing changes underneath the skin and may help identify in ammatory variables that lead to PIVC failure.…”
Section: Introductionmentioning
confidence: 99%